Pengaruh Fashion Involvement dan Hedonic Shopping Motivation Terhadap Impulse Buying pada Retail Fashion Uniqlo di Karawang - Fadhilah Fatin; Netti Nurlenawati; Dexi Triadinda (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The aim of the research is to analyze impulse buying (IB) at Uniqlo fashion retail in Karawang which can be influenced by fashion involvement (FI) and hedonic shopping motivation (HSM). Using a quantitative approach with a verification survey method. Data analysis was carried out using the path analysis method or path analysis with smart pls. Research shows that fashion involvement (FI) and hedonic shopping motivation (HSM) have a significant and positive effect. However, there is no direct effect between fashion involvement (FI) and impulse buying (IB), but there is a direct effect between hedonic shopping motivation (HSM) and impulse buying (IB). Apart from that, it was also found that there was direct effect between fashion involvement (FI) and impulse buying (IB) through hedonic shopping motivation (HSM). The conclusion was that the higher a person's level of fashion involvement (FI) and hedonic shopping motivation (HSM), the higher the possibility of them doing impulse buying (IB) at Uniqlo fashion retail in Karawang. The implications of this research can provide insight for fashion retail managers to better understand consumer behavior in the context of impulse buying (IB) and consider appropriate marketing strategies to increase sales.